Nutrient harvest and soil fertility as influenced by legume-wheat (Triticum aestivum) sequences - PARSAD, N K; KUMAR, SANJAY (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1993-95 to assess the contribution of preceding legume crop on succeeding wheat (Triticum aestivum L. emend. Fiori & Paol) for crop production, nutrient harvest and balance of the same in soil under recommended doses of nutrients of kharif crops and variable levels of nitrogen to succeeding wheat. Blackgram phasea/us mango L.) as a preceding crop to wheat resulted in the maximum wheat production while stylo (Stylosanthes hamata L.) wheat sequence accounted for higher wheat equivalent yield. Application of 75 kg N/ha to wheat grown after legume was as good as to wheat yield received at 100 kg N/ha after legume. Soybean (Glycine max (L.) Merr.)wheat sequence has removed the maximum quantity ofN while wheat grown after blackgram harvested the maximum quantity of N. Soybean - wheat sequence further removed the highest quantity of P but stylo - wheat sequence recorded the maximum recovery of K. Though all the legume - wheat sequences have recorded better build up in soil N, however, wheat grown after blackgram at 100 kg N/ha recorded the maximum build up in available soil N while wheat grown in absence of extemal N has left over maximum available P in soil. General increase in available K was noticed under all the sequences to their initial status.